Edukasi Makanan Tinggi Serat Rendah Gula mencegah Kejadian Keputihan Pada Remaja Mahasiswa Kebidanan Tingkat 1 & II Universitas Zainul Hasan Probolinggo - Iit Ermawati (Rena Cipta Mandiri, 2025)
Vaginal discharge is a symptom commonly experienced by most women. Knowledge about reproductive health is important to impart to adolescents. Adolescents need to be equipped with various knowledge, attitude development, and self-skills related to reproductive health to support positive development. The problem faced by adolescents is that they do not know what types of food to avoid when experiencing vaginal discharge. Women of childbearing age, especially adolescents, must pay close attention to their reproductive health. The activity conducted on July 24, 2025 aims to To increase female students' knowledge about high-fiber and low-sugar foods to prevent vaginal discharge by knowing the types of foods to avoid during vaginal discharge will prevent adolescents from experiencing vaginal discharge. Vaginal discharge is a problem experienced by more than 75% of women in the world, with about 60% of vaginal discharge complaints coming from women under the age of 22 and 40% from women under the age of 45. Education on high-fiber, low-sugar foods prevents vaginal discharge in adolescents. The education method is carried out through field observations, interviews, and socialization. The method of activity is to provide education on high-fiber, low-sugar foods to prevent vaginal discharge. The indicator of program success is to increase female students' knowledge and ability to choose the right type of food when experiencing vaginal discharge. The output of the Community Partnership Program is the publication of articles in national journals.